The Possible Emergence of an Attractive Inverse-Square Law from the Wave-Nature of Particles - Dong Zhang; Pavel Kroupa; Jan Pflamm-Altenburg; Manfred Schmid (Advances in High Energy Physics)
A model of a particle in finite space is developed and the properties that the particle may possess under this model are studied. The possibility that particles attract each other due to their own wave nature is discussed. The assumption that the particles are spatially confined oscillations (SCO) in the medium is used. The relation between the SCO and the refractive index of the medium in the idealized universe is derived. Due to the plane wave constituents of SCOs, the presence of a refractive index field with a nonzero gradient causes the SCO to accelerate. The SCO locally changes the refractive index such that another SCO is accelerated towards it, and vice versa. It is concluded that the particles can attract each other due to their wave nature and an inverse-square-type acceleration emerges. The constant parameter in the inverse-square-type acceleration is used to compare with the gravitational constant GN, and the possibility of non inverse-square-type behavior is preliminary discussed.